Gender-specific approaches, rural institutions and technological innovations - Ragasa, Catherine; Sengupta, Debdatta; Osorio, Martha; OurabahHaddad, Nora; Mathieson, Kirsten (Food and Agricultural Organization of the United Nations, 2014)
This paper reviews and integrates findings from existing empirical studies and case studies received from 35 organizations in various countries to identify demand- and supply-side constraints and opportunities in access, adoption and impact of agricultural technological innovations. The most common technologies studied are improved seeds, fertilizers, farm mechanization, improved management practices, transporting technologies, and information and communication technologies. This review consistently finds that women have much lower observed rates of adoption of a wide range of technologies than men; and these are mainly due to differentiated access to complementary inputs and services. There are limited studies that looked at upstream stages including priority-setting and innovation processes, in which women continue to be underrepresented.